The stabilization of clay soil using wood sawdust ash and its effect against unconfined compressive strength (UCS) value - Mina, Enden; Kusuma, Rama Indera; Fathonah, Woelandari; Ashari, Salsabila Joesi Nur (Jurnal Teknika, 2023)
Soil is the basis for the construction of roads, buildings, dams, and embankments. Construction activities on roads cannot be separated from soil works on which the infrastructure was built. This study aims to improve (stabilize) clay soil by taking a location in Juhut Village, Pandeglang Regency using sawdust ash from meranti wood. The effect of the addition of sawdust ash was studied against the unconfined compressive strength value of the soil and its properties using several variations of the mixture. The mix variations used in this study use sawdust wood ash percentages of 0%, 5%, 10%, and 15%. The effect of the mixture on soil properties was investigated by tested the physical and mechanical properties through soil classification test, Atterberg limits tests, specific gravity tests, compaction tests, and unconfined compressive strength tests. The results of analysis and laboratory tests show that the soil can be classified as clay with moderate to high plasticity (OH) based on the USCS classification. The optimum value of unconfined compressive strength was obtained by adding variations of sawdust wood ash obtained at 15% variation of wood sawdust ash with 28 days of curing time of 3.790 kg/cm2. While the soil plasticity index value decreased from 22.8% to 7% with the addition of sawdust wood ash at a percentage of 15%. Therefore, it can be concluded that the addition of sawdust wood ash for soil stabilization could increase a good effect on soil strength.